Contributions of Kerim Kerimov in aerospace engineering - Mohamad, Masturah; Othman, Raihan (IIUM Press, 2011)
The objective ofthis research is to study the contributions ofthe person behind Rusia's achievement in space exploration. The significance of this chapter shows that a good leader is important to ensure the all missions are performed smoothly, capable to overcome and rectify problems quickly. The methodology adopted in this chapter is based on data collection from library and other trustworthy sources. This chapter explores early development and achievement in space exploration during Kerim Kerimov's life. Prior to 1987, Kerim Kerimov was not known to public even though his contributions in space research were vast. He had dedicated himself to the space researches throughout his life and contributed to the development of space exploration in his country. For more than 25 years involvement in aerospace industry, he had launched many astronauts and spacecrafts such as Vostok 1, Molniya, Soyuz 11 and so on. However, not all missions were successfully accomplished. Failure teaches people to be more creative, innovative and dare to take risks because there is no victory without efforts